1999
DOI: 10.1063/1.125559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interfacial oxides on Schottky barrier contacts to n- and p-type GaN

Abstract: Schottky contacts were formed on n- and p-type GaN after either a conventional surface cleaning step in solvents, HCl and HF or with an additional treatment in (NH4)2S to prevent reformation of the native oxide. Reductions in barrier height were observed with the latter treatment, but there was little change in diode ideality factor. A simple model suggests that an interfacial insulating oxide of thickness 1–2 nm was present after conventional cleaning. This oxide has a strong influence on the contact characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 14 publications
3
45
0
Order By: Relevance
“…In addition, the work done by Liu et al has shown that the Ga peak becomes larger when samples are cleaned in (NH 4 ) 2 S than in HF/HCl [15]. Furthermore, (NH 4 ) 2 S has been found to reduce the barrier height on GaN, and preventing re-oxidation of the surface [16]. We suggest that there exist Ga-Cl and Ga-S on sample 1 and sample 2, respectively.…”
Section: Diale Fd Auret / Physica B ] (]]]]) ]]]-]]]mentioning
confidence: 54%
“…In addition, the work done by Liu et al has shown that the Ga peak becomes larger when samples are cleaned in (NH 4 ) 2 S than in HF/HCl [15]. Furthermore, (NH 4 ) 2 S has been found to reduce the barrier height on GaN, and preventing re-oxidation of the surface [16]. We suggest that there exist Ga-Cl and Ga-S on sample 1 and sample 2, respectively.…”
Section: Diale Fd Auret / Physica B ] (]]]]) ]]]-]]]mentioning
confidence: 54%
“…[7][8][9][21][22][23][24] The activation energy of the Mg acceptor level is taken at ͑ E t -E v )ϭ0.16 eV. The Schottky barrier height q b is taken 0.70 eV.…”
Section: A Schottky Gan:mg Junction Under Room Temperature Zero-biamentioning
confidence: 99%
“…The Schottky barrier height q b is taken 0.70 eV. [21][22][23] The hole surface recombination velocity is taken 10 9 cm/s. Fig.…”
Section: A Schottky Gan:mg Junction Under Room Temperature Zero-biamentioning
confidence: 99%
“…In particular, leakage currents through Schottky contacts not only impede device reliability but also degrade power efficiency and noise performance in such devices. In spite of the fact that Schottky diodes formed on GaN and AlGaN are suffering from excess reverse leakage currents that are many orders of magnitude larger than the prediction of the thermionic emission ͑TE͒ model, [1][2][3][4][5][6] only a few studies have focused on the reverse-current characteristics quantitatively.…”
mentioning
confidence: 99%